The interaction of C60 and its derivatives with a lipid bilayer via molecular dynamics simulations. - D'Rozario, R; Wee, C; Wallace, E; Sansom, MS (2009)
Coarse-grained molecular dynamics simulations have been used to explore the interactions of C(60) and its derivatives with lipid bilayers. Pristine C(60) partitions into the bilayer core, whilst C(60)(OH)(20) experiences a central energetic barrier to permeation across the bilayer. For intermediate levels of derivatization, e.g. C(60)(OH)(10), this central barrier is smaller and there is an energetic well at the bilayer/water interface, thus promoting entry into cells via bilayer permeation whilst maintaining solubility in water.